2012
DOI: 10.1097/cmr.0b013e32834e6a67
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex ligation-dependent probe amplification equals fluorescence in-situ hybridization for the identification of patients at risk for metastatic disease in uveal melanoma

Abstract: In uveal melanoma, loss of chromosome 3 and gain of chromosome 8q are associated with a high risk of metastasis. In this study, we validated the use of multiplex ligation-dependent probe amplification (MLPA) in detecting patients at risk for metastatic disease in comparison with the predictive power of fluorescence in-situ hybridization (FISH). For 64 uveal melanoma samples, the MLPA results of chromosome 3 and 8 were compared with the results obtained by FISH. For seven samples, a single nucleotide polymorphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 26 publications
0
33
0
Order By: Relevance
“…48 In a study using multiplex ligation-dependent probe amplification (MLPA) to detect chromosome 3 loss, 10-year disease-specific mortality was 0% in 133 tumors without chromosome 3 loss. 50 Although these authors did not directly compare MLPA with other techniques, Vaarater et al 51 demonstrated that MLPA was equivalent to FISH for the identification of patients at risk for metastatic disease in uveal melanoma. The sensitivity of MLPA to detect patients at risk for metastatic disease was higher than that of FISH (0.795 vs. 0.692) but the specificity was equal for both techniques (0.840).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…48 In a study using multiplex ligation-dependent probe amplification (MLPA) to detect chromosome 3 loss, 10-year disease-specific mortality was 0% in 133 tumors without chromosome 3 loss. 50 Although these authors did not directly compare MLPA with other techniques, Vaarater et al 51 demonstrated that MLPA was equivalent to FISH for the identification of patients at risk for metastatic disease in uveal melanoma. The sensitivity of MLPA to detect patients at risk for metastatic disease was higher than that of FISH (0.795 vs. 0.692) but the specificity was equal for both techniques (0.840).…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of MLPA to detect patients at risk for metastatic disease was higher than that of FISH (0.795 vs. 0.692) but the specificity was equal for both techniques (0.840). 51 Onken et al 18 reported that loss of heterozygosity of chromosome 3 detected by SNP-A was superior to that of FISH in predicting metastatic outcome. However, FISH analysis was suboptimal in that study because investigators used paraffinembedded tissue (replete with truncation artifacts) and counted only 100 cells.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33] At present, the method of choice for initial chromosomal analysis is multiple ligation probe amplification (MLPA), which probes multiple loci across several chromosomes. [31][32][33][34] If the result contradicts the histopathological grade, reanalysis with methods such as complete genomic hybridization is advisable. 31,33 Advantages of MLPA include low cost and data obtained simultaneously from several chromosomes other than chromosome 3.…”
Section: Prognosis Of the Primary Tumourmentioning
confidence: 99%
“…These alterations were initially identified by standard karyotypic analyses. 94 79,[125][126][127] and singlenucleotide polymorphisms (SNPs). 109,[128][129][130][131][132] The above-mentioned chromosomal alterations in primary UM are clinically relevant because of their correlation with the risk of metastatic death.…”
Section: Chromosomal Alterations In Primary Ummentioning
confidence: 99%